Photophysics and photochemistry of 1,2,3-triazole-based complexes - Scattergood, Paul A.; Sinopoli, Alessandro; Elliott, Paul I.P. (Coordination chemistry reviews, 2017)
[Display omitted] •Triazole-based ‘click’ chemistry is a versatile tool in ligand design.•Triazole-based ligands enable access to rich coordination chemistry.•Facile tuning of photophysical luminescent properties through ‘click’ chemistry design.•Diverse applications from cellular imaging to light-emitting and photovoltaic devices.•Triazole-based ligand enables access to highly novel photochemistry. The copper-catalysed cycloaddition of alkynes and azides to form 1,2,3-triazoles has emerged as a powerful tool in ligand design and the synthesis of novel transition metal complexes. In this review we focus on the photophysical properties of metal complexes bearing 1,2,3-triazole-based ligands with a particular emphasis on those of d6 metals including rhenium(I), iron(II), ruthenium(II), osmium(II) and iridium(III). We also highlight key examples of triazole complexes of platinum(II) and palladium(II) as well as the lanthanides and coinage metals.